Immunization with the immunodominant Helicobacter suis urease subunit B induces partial protection against H. suis infection in a mouse model - Vermoote, Miet (BioMed Central, 2012)
Helicobacter (H.) suis is a porcine and human gastric pathogen. Previous studies in mice showed that an H. suis infection does not result in protective immunity, whereas immunization with H. suis whole-cell lysate (lysate) protects against a subsequent experimental infection. Therefore, two-dimensional gel electrophoresis of H. suis proteins was performed followed by immunoblotting with pooled sera from H. suis- infected mice or mice immunized with lysate. Weak reactivity against H. suis proteins was observed in post-infection sera. Sera from lysate-immunized mice, however, showed immunoreactivity against a total of 19 protein spots which were identified using LC-MS/MS. The H. suis urease subunit B (UreB) showed most pronounced reactivity against sera from lysate-immunized mice and was not detected with sera from infected mice. None of the pooled sera detected H. suis neutrophil-activating protein A (NapA). The protective efficacy of intranasal vaccination of BALB/c mice with H. suis UreB and NapA, both recombinantly expressed in Escherichia coli (rUreB and rNapA, respectively), was compared with that of H. suis lysate. All vaccines contained choleratoxin as adjuvant. Immunization of mice with rUreB and lysate induced a significant reduction of H. suis colonization compared to non-vaccinated H. suis-infected controls, whereas rNapA had no significant protective effect. Probably, a combination of local Th1 and Th17 responses, complemented by antibody responses play a role in the protective immunity against H. suis infections.